Kraft and Soda Pulping of White Rot Pretreated Betung Bamboo - Widya Fatriasari; Riksfardini A Ermawar; Faizatul Falah; Dede HY Yanto; Deddy TN Adi; Sita H Anita; Euis Hermiati (Masyarakat Peneliti Kayu Indonesia, 2011)
This research was conducted to study the effects of pre-treatment with white-rot fungi on pulp properties of betung bamboo. Inoculum stocks of white-rot fungi (25 ml) were injected into polybags contained barkless fresh bamboo chips. Each polybag contained 214.9–286.8 g oven dry weight of chips. Bamboo chips in the polybags were inoculated by Pleurotus ostreatus and Trametes versicolor. Both of them were then incubated for 30 and 45 days at room temperature. Bamboo chips were cooked using soda and Kraft processes. The cooked bamboo chips were then defiberize using disc refiner for 3 times. Pulp yield, kappa number and degree of freeness of the pulp were then analyzed. The treatment of two white rot fungi, gave different effects on the characteristic of betung bamboo pulp. The effects of fungi treatment on kappa number and degree of freeness can be seen only at samples cooked using kraft process. Incubation time did not affect pulp yield of bamboo treated with both fungi, but it affected kappa number and degree of freeness of bamboo pulp cooked using kraft process. Bamboo treated with T. versicolor incubated for 45 days and cooked using kraft process produced the best pulp quality with high pulp yield.Key words: betung bamboo, biopulping, degree of freeness, kappa number, pulp yield.